Spuriously high free thyroxine with the Amerlite MAB FT4 assay. Issue 2 (February 1994) - Lai, L C; Day, J A; Clark, F; Peaston, R T
Abstract : In the Amerlite MAB FT4 assay, as stated by the manufacturer, FT4 values should be normal in patients with anti-thyroid hormone autoantibodies. The case of a 69 year old woman with a spuriously high FT4 using the Amerlite MAB FT4 assay is reported. Laboratory investigations showed that her spurious FT4 result was likely to have been caused by anti-thyroid hormone autoantibodies.